2014
DOI: 10.1002/jsfa.6860
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the drivers of liking by investigating the reasons for (dis)liking using CATA in cross‐cultural context: a case study on barbecue sauce

Abstract: Reasons for (dis)liking CATA proved to be a powerful supporting method to understand the internal drivers of liking which can be overlooked by generic descriptive analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…Furthermore, it is worth noting that although the general trend for overall liking and familiarity did not significantly differ between the 2 age groups (Table ), the overall liking and familiarity scores for the traditional‐type samples (TSB1 and TSB2) tended to be lower for YC than OC consumers. Product familiarity is one of the most important determinants influencing the overall liking of consumers for a traditional fermented food such as Doenjang (Choi et al., ; Chung et al., ; Hong et al., ; Jang et al., ; Yusop, O'Sullivan, Kerry, & Kerry, ). Because the present OC consumers were more likely to be exposed to such products, these consumers seemed to accept traditional‐type products better than did the YC consumers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is worth noting that although the general trend for overall liking and familiarity did not significantly differ between the 2 age groups (Table ), the overall liking and familiarity scores for the traditional‐type samples (TSB1 and TSB2) tended to be lower for YC than OC consumers. Product familiarity is one of the most important determinants influencing the overall liking of consumers for a traditional fermented food such as Doenjang (Choi et al., ; Chung et al., ; Hong et al., ; Jang et al., ; Yusop, O'Sullivan, Kerry, & Kerry, ). Because the present OC consumers were more likely to be exposed to such products, these consumers seemed to accept traditional‐type products better than did the YC consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, when the samples were evaluated in soup, which is a form that is more familiar to consumers, the expectations may have played more important role, thus resulted in discrepancy in familiarity and preference for traditional‐type samples between YC and OC. Considering the importance of familiarity in association to expectation (Piqueras‐Fiszman & Spence, ) and overall acceptability of a product (Choi et al., ; Chung et al., ; Hong et al., ; Jang et al., ; Laing et al., ; Pagès, Bertrand, Ali, Husson, & Lê, ; Prescott, ; Prescott et al., , ; Yusop et al., ), assessing consumer responses for the representative consumed form can be critical for understanding the drivers of liking for condiments such as Doenjang .…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] In contrast to the extensive sensory research into fresh fruits, there have been relatively few cross-cultural studies aimed at understanding the drivers that lead to liking of fresh fruit, in part due to the limitations of keeping fruit fresh at the testing sites in different countries. Instead, cross-cultural studies have been conducted extensively with processed or cooked food items, 5,[20][21][22][23] because understanding consumer liking and perceptions of target food items in a cross-cultural context is essential when food producers aim to export their foodstuffs to different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Choi et al . () reported that drivers of liking could be explained better, when external drivers (sensory vocabularies elicited by trained panelists) are complemented by internal drivers that were derived from consumers using CATA questions. The use of CATA in parallel with descriptive analysis can facilitate a more holistic understanding of the concept of nuttiness by providing supplementary information on consumer perceptions and expressions of nuttiness.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of consumer-based profiles with a descriptive profile can uncover sensory dimensions that are important for consumers, as well as differences in verbalizations and perceptions between trained panelists and consumers. Recently, Choi et al (2014) reported that drivers of liking could be explained better, when external drivers (sensory vocabularies elicited by trained panelists) are complemented by internal drivers that were derived from consumers using CATA questions. The use of CATA in parallel with descriptive analysis can facilitate a more holistic understanding of the concept of nuttiness by providing supplementary information on consumer perceptions and expressions of nuttiness.…”
Section: Introductionmentioning
confidence: 99%